Community organisation-researcher partnerships: what concerns arise for community organisations and how can they be mitigated?. Issue 10 (2nd July 2020) - Pratt, Bridget
Abstract : Universities and research funders' growing emphasis on community partnerships, engagement and outreach has seen a rise in collaborations between university researchers and staff of community organisations (COs) on research projects. What ethical issues and concerns are experienced as part of these collaborations has largely not been described, particularly from the perspective of COs . As part of a recent, broader qualitative study, several concerns arising during health research collaborations between COs and university researchers were captured during thematic analysis. The concerns were described in semistructured interviews by four staff of three COs that work with marginalised groups (ie, migrants and refugees, women who experience domestic violence, indigenous populations) in a high-income country. In this paper, the three concerns are taken as the starting point for ethical analysis. Interview data are first used to illustrate the three concerns: being restricted to a recruitment role in studies, reinforcement of stereotypes of marginalised groups and weakening CO-community relationships. The paper then explores why the concerns are morally troubling and demonstrates how each concern generates feelings of disrespect, creates harm(s), and/or reflects or reinforces unfairness or injustice. It concludes by proposing three ethical criteria for CO-researcher partnerships: fair division of labour, balancing CO advocacy goals with research goals and balancing CO service goals with research goals. Where researchers and COs discuss how to meet these criteria at the start and during research collaborations, it can potentially help mitigate or prevent the occurrence of the concerns described in this paper.